Evaluation of root dentin damage during retreatment procedure using various engine-driven retreatment file systems-A micro-CT study - Eby Varghese; Naman Awasthi; Pranitha Kakarla; Shilpa Mailankote; Debasish Mishra; Nishin K John (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this research was to assess the damage to root dentin that arises from retreatment with different engine-driven NiTi retreatment files employing micro-computed tomography. Materials and Methods: Sixty mandibular premolar teeth having a single root and root canal that were recently extracted were gathered and stored. The specimens were de-coronated at the cementoenamel junction under water irrigation to achieve a homogeneous root length of 16 millimeters. Gutta-percha cones were coated with sealants and placed within the radicular canal till the WL. All sixty premolars were randomly assigned to one of the following three groups, with every group comprising 20 sample teeth each. Group 1: MTwo Retreatment files, Group 2: ProTaper Universal Retreatment files, Group 3: Edge File XR Retreatment rotary files. The quantity of root dentinal injury was estimated by deducting the dentin volume (mm3) in the pre- and post-therapy micro-CT scans at apical, middle, and cervical 3rd points. Results: An intra-group comparative scrutiny showed that lower radicular dentinal injury was noted at apical 3rd (0.31 ± 0.16, 0.62 ± 0.02) in Edge File XR Retreatment file system and MTwo Retreatment file system in that order. The statistically significant disparity was seen amid the MTwo Retreatment file, Edge File XR Retreatment file system and ProTaper Universal Retreatment file, Edge File XR Retreatment file system with P value of 0.001on intergroup assessment. Conclusion: In spite of the limitations that this research had, it was inferred that each assessed file system proficiently eradicated the obturated material through the retreatment procedure performed. In addition, it was seen that the Edge File XR group showed lesser root dentin damage in contrast to MTwo and ProTaper Universal file systems.